Distributed real-time power management of high-penetrated PV sources with voltage regulation over time-varying networks. (July 2021) - Kang, Wenfa; Chen, Minyou; Lai, Wei; Luo, Yanyu
Highlights: The proposed distributed control methods for PV inverters minimize system active and reactive power costs. System voltage limits violations are avoided by introducing local dynamic economic parameter. The proposed distributed algorithms can be applied over the time-varying directed communication graphs. The convergence and optimality of proposed algorithms are studied in detailed mathematical analysis. Abstract: The growing penetration of photovoltaic (PV) sources accommodated in Active Distribution Network (ADN) brings various severe voltage limits violation problems. This paper provides power management strategy for PV inverters in order to achieve power sharing as well as voltage regulation by dispatching PV active and reactive power. The proposed power management method can operate in a fully distributed manner where each unit measures local voltage information and communicates with neighboring units via time-varying directed communication networks to make its decisions, minimize the PV operation costs, drive system voltage into an acceptable range and always meet the active and reactive capacity constraints. The effectiveness and performance of the proposed method are validated by running different simulation scenarios on a real-time simulator (OPAL-RT).